찰옥수수와 단옥수수간 교잡으로부터 유래된 F2:3 집단에서 수량 및 식미관련 형질의 유전분석 - 박기진(Ki Jin Park); 이주경(Ju Kyong Lee); 사규진(Kyu Jin Sa); 고희종(Hee Jong Koh) (Korean journal of breeding, 2012)
식용 풋찰옥수수 고품질 육종에 관련된 주요 형질들의 특성을 파악하고자 수행한 본 연구는 모계 02S6140(찰옥수수, SSww)와 부계 KSS22(단옥수수, ssWW)의 교잡(F1)에서 분리된 F2 집단에서 수량 및 식미관련 형질들의 유전적 특성을 조사하였다. 그 결과 출사일수는 모본(02S6140) 계통이 85일, 부본(KSS22) 계통이 66일로 현저한 차이가 있었지만, F1은 71일로 교배친의 평균값 75.5일보다 작아지는 방향으로 나타났다. 간장(PH)은 F1에서 159 cm, 모부의 평균값 95 cm와 비교하여 크게 나타났다. 착수고율은 F2 집단의 평균이 교배친의 평균값 44와 동일하였고 찰질이 일반질 옥수수보다 높은 것으로 나타났다. 과피두께는 F1, F2 계통들에서 71 μm과 74 μm로 나타나 모부의 83.5 μm 평균보다 얇아지는 방향으로 나타났다. 아밀로스함량은 입질별로 매우 유의하게 차이가 있어 일반질이 평균 14.0%로 가장 높았으며 당질은 7.4%, 찰질은 5.0%의 값을 보였으며, 아밀로스함량에 대한 F1의 잡종강세는 비교적 높은 116.1의 값을 보였다. 유전자형 suwx는 이중열성돌연변이로 표현형은 sugary로 나타났다. This research was conducted to understand yield components and taste-associated traits for high quality waxy corn breeding using 158 F2:3 families of a crossing between sugary (KSS22) and waxy inbred (02S6140). This material complied with Mendel’s dominant and segregation law, was all normal kernel in F1, and the ratio of kernel types was 9 of normal, 4 of sugary, 3 of waxy in F2 seeds. Days to silking from sowing for F1 were seventy one days, earlier than seventy six days for parents and F2 families. Pericarp thickness in F1:2 and F2:3 seeds were 71 and 74 μm, respectively, thinner than parental average of 83.5 μm, therefore pericarp thickness of early progenies derived from a crossing of waxy parent (02S6140, 116 μm) and sugary parent (KSS22, 51 μm) skewed with the thin parent, KSS22. The average amylose content of sugary kernel genotypes ranged 2.3% to 10.8%, especially 2.3% for sugary kernel of susuwxwx genotype, showing significantly low content. In comparison with waxy kernel phenotype in F2:3 families, the waxy type segregated with double mutant sugary together had the amylose content of 5.4% compared with the other waxy families segregated from waxy or normal F2 kernel. It was much lower than the amylose content of waxy parent 02S6140, which has 6.6%. The broad-sense heritability of pericarp thickness was 0.82, indicating that we can breed high quality waxy corn with thinner pericarp and higher amylopectin content compared with the parents.